Research on the Time Course of River Water Quality with Runoff in Urban Area - LIU Zhijun; LYU Wenbin; WANG Bin; PAN Wenwei (Renmin Zhujiang)
Deterioration of river water quality during rainfall is a difficult problem for water environment treatment,and it is of great significance to study its change rules during rainfall.Taking the canal area of Guangzhou-Shenzhen Railway in Guangzhou Liede River as the research object,this paper collects river water samples during the rainfall period,detects various index data,and establishes runoff-pollution relationship by combining flow data and dimensionless curve method.The results show that the Liede River is not only affected by first flush in the early stage but also polluted by pipe scouring in the middle and late stages.The pollution caused by the latter is 2~5 times that of the former;COD and TN at first flush is serious,and TP and SS are less,but the four pollutants in pipe scouring pollution are more prominent;pipe scouring pollution and first flush are affected by changes in rainfall characteristics and water flow conditions.